2015
DOI: 10.1371/journal.ppat.1004636
|View full text |Cite|
|
Sign up to set email alerts
|

The M3 Muscarinic Receptor Is Required for Optimal Adaptive Immunity to Helminth and Bacterial Infection

Abstract: Innate immunity is regulated by cholinergic signalling through nicotinic acetylcholine receptors. We show here that signalling through the M3 muscarinic acetylcholine receptor (M3R) plays an important role in adaptive immunity to both Nippostrongylus brasiliensis and Salmonella enterica serovar Typhimurium, as M3R-/- mice were impaired in their ability to resolve infection with either pathogen. CD4 T cell activation and cytokine production were reduced in M3R-/- mice. Immunity to secondary infection with N. br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…Of increasing interest, type 3 muscarinic receptors (M3Rs) have received significant attention for their key role in maintaining mucosal barrier function (122) and in regulating mucin production and secretion within the GI tract (123). In addition, M3Rs contribute to host defense against N. brasiliensis (124,125) and C. rodentium (121). Despite N. brasiliensis infection, mice deficient in the muscarinic acetylcholine receptor M3 (Chrm3 −/− ) show an absence of typical goblet cell expansion (125).…”
Section: Enteric Nervous System Regulationmentioning
confidence: 99%
“…Of increasing interest, type 3 muscarinic receptors (M3Rs) have received significant attention for their key role in maintaining mucosal barrier function (122) and in regulating mucin production and secretion within the GI tract (123). In addition, M3Rs contribute to host defense against N. brasiliensis (124,125) and C. rodentium (121). Despite N. brasiliensis infection, mice deficient in the muscarinic acetylcholine receptor M3 (Chrm3 −/− ) show an absence of typical goblet cell expansion (125).…”
Section: Enteric Nervous System Regulationmentioning
confidence: 99%
“…Cholinergic signalling suppresses expression of inflammatory cytokines by macrophages via α7 nicotinic receptors (nα7R) [33], whereas ligation of the m3 muscarinic receptor (m3R) on CD4+ T cells potentiates cellular activation and cytokine production [11]. It was thus unclear what effect secreted AChEs might have on the immune response to an infectious agent.…”
Section: Discussionmentioning
confidence: 99%
“…B cells also release ACh which acts on endothelial cells to inhibit expression of integrins and thus suppress inflammatory extravasation of neutrophils [10]. In contrast to these anti-inflammatory effects of ACh on innate immunity, we recently showed that ACh acts as a co-stimulatory signalling molecule for CD4+ T cell activation and cytokine production [11]. Cholinergic signalling in relation to immunity is thus complex and multi-layered, and it is difficult to predict what effect parasite secreted AChEs might have in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Cholinergic signaling plays a role in a number of immune cell functions, including acting as a costimulatory factor for T lymphocyte activation and cytokine secretion (Darby et al . ), and there are many ways in which AChEs could inhibit or modulate these responses. Alternatively, secreted AChEs could protect against inhibitors ingested in foodstuffs, i.e.…”
Section: Amplification Of Ache Genes In Parasitic Nematodesmentioning
confidence: 99%